Accessibility and Challenges of Inclusive Education Curriculum Standars in Indonesia: A Systematic Literature Review - Muzayanah, Umi; Wasino, Wasino; Wahyudin, Agus; Sofanudin, Aji; Maknun, Moch. Lukluil; Santoso, Arif Gunawan (Universitas Negeri Semarang, 2025)
This study aims to examine the implementation of inclusive curriculum standards in promoting educational equity in Indonesia, identify strategies to enhance educational accessibility for students from disadvantaged backgrounds, particularly in the context of content standards, and investigate the challenges in developing inclusive curricula. Employing a Systematic Literature Review (SLR) methodology, the study analyzes 50 scholarly articles from reputable academic databases, including Google Scholar, Web of Science (WoS), and Lens. The findings indicate that inclusive education aspires to provide equitable access to education for all children, including those with special educational needs, with the goal of optimizing each student's potential and fostering a more tolerant and inclusive society. In Indonesia, inclusive education is supported by a range of policies that offer a legal foundation for its implementation. Several strategies have been adopted to improve accessibility to quality education for students with special needs, including the development of inclusive curriculum standards, inter-sectoral collaboration, and efforts to improve infrastructure and teacher capacity. Nevertheless, the implementation of inclusive curricula continues to face significant challenges, such as inadequate facilities, limited teacher training, persistent social stigma, and difficulties in tailoring curricula to meet the diverse needs of learners. The success of inclusive education depends on largely on the collaborative commitment of key stakeholders, government bodies, educational institutions, communities, and families, to cultivate a truly inclusive learning environment. This study underscores the critical importance of shared responsibility and sustained engagement in overcoming these barriers to achieve equitable and inclusive education for all children in Indonesia.